Studenten skal bli lærer Kunnskap, identitet og profesjonsutvikling - Løhre, Audhild (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2020)
"The student is becoming a teacher is presenting the first Norwegian study made on the sense of belonging in higher education. Central themes are comprehension and knowledge development, and the students' process of formation is essential, without it being explicit in all the articles. The authors are concerned with interplay between techne and fronesis related to individual growth and professional development. The informants of these studies are teacher students from year 1-4, resulting in a wide range of new knowledge and theoretical viewpoints. In this anthology, the question of the dualism between theory and practice is raised. Could it be that knowledge is a circular production from practise to theory and back? It is also evident that the sensation of social belonging is closely connected to a sense of academic belonging, and that the cohesion of teacher students and their teachers is of great impact. The target group of this peer-reviewed anthology is teacher students and teacher student educators. However, these articles will also be relevant for other educational groups and students. "